2014
DOI: 10.1037/a0034060
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical switch costs in bilingual language production induced by reading words.

Abstract: We examined language-switching effects in French-English bilinguals using a paradigm where pictures are always named in the same language (either French or English) within a block of trials, and on each trial, the picture is preceded by a printed word from the same language or from the other language. Participants had to either make a language decision on the word or categorize it as an animal name or not. Picture-naming latencies in French (Language 1 [L1]) were slower when pictures were preceded by an Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
109
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(136 citation statements)
references
References 26 publications
15
109
4
1
Order By: Relevance
“…However, Peeters et al (2014) showed comprehension to production switch costs using a paradigm in which participants performed an explicit task on input words. The authors assume that comprehension of input words activates language nodes automatically (i.e., it operates as an exogenous factor, in BIA's terminology).…”
Section: Switch Costs In Production Comprehension and Across Modalimentioning
confidence: 99%
See 3 more Smart Citations
“…However, Peeters et al (2014) showed comprehension to production switch costs using a paradigm in which participants performed an explicit task on input words. The authors assume that comprehension of input words activates language nodes automatically (i.e., it operates as an exogenous factor, in BIA's terminology).…”
Section: Switch Costs In Production Comprehension and Across Modalimentioning
confidence: 99%
“…But since longer preparation times lead to reduced switch costs in language production (Declerck, Philipp, & Koch, 2013), we decided to avoid the use of cues (note that the language in which a word would appear was not pre-cued in Peeters et al, 2014).…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…This refers to switch costs being larger when switching into L1 than when switching into L2 (e.g., Jin, Zhang, & Li, 2014;Macizo, Bajo, & Paolieri, 2012;Meuter & Allport, 1999;Philipp et al, 2007;Peeters, Runnqvist, Bertrand, & Grainger, 2014;Verhoef et al, 2009; for a review, see Bobb & Wodniecka, 2013). The most prevalent explanation of this effect is based on the ICM (Green, 1998), which assumes reactive, persisting inhibition to occur during language control.…”
Section: Asymmetrical Switch Costs As a Marker For Inhibitionmentioning
confidence: 99%